Artificial nail composition and artificial nail
Patent Information
- Application Number
- JP2026030078
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2025-03-31
- Filing Date
- 2026-02-26
- Publication Date
- 2026-10-14
AI Technical Summary
【0014】 本発明によれば、光沢を抑制したマット感及び滑らかな触感を有する人工爪を形成するための人工爪組成物を提供することが可能である。
Smart Images

Figure 2026167484000001 
Figure 2026167484000002 
Figure 2026167484000003
Abstract
Description
TECHNICAL FIELD
[0001] The present invention relates to an artificial nail composition and an artificial nail. BACKGROUND ART
[0002] Among artificial nails such as nail polish, gel nails, and acrylic nails, gel nails are widely used from the perspectives of good workability, long-term retention on nails or artificial nails, and low odor. As one of the gel nail designs, gel nails with a matte feel that suppresses gloss (non-glossy) are in demand, and as one of the methods for realizing such matte gel nails, there is a method of adding a filler to a photocurable artificial nail composition to create irregularities on the surface of the cured film, thereby suppressing gloss by causing diffuse reflection of light.
[0003] Patent Document 1 describes that an artificial nail composition with suppressed gloss can be obtained by containing a compound having a (meth)acryloyl group, a photoinitiator, and (meth)acrylic polymer particles. PRIOR ART DOCUMENTS PATENT DOCUMENTS
[0004] PATENT DOCUMENT 1 Japanese Patent No. 7014970 SUMMARY OF THE INVENTION PROBLEMS TO BE SOLVED BY THE INVENTION
[0005] While the artificial nail composition of Patent Document 1 has a matte feel with suppressed gloss, it has problems such as poor smoothness of the surface of the cured coating film. As described above, it has been difficult for conventional artificial nail compositions to achieve both a matte feel and a smooth tactile sensation.
[0006] An object of the present invention is to provide an artificial nail composition for forming an artificial nail having a matte feel with suppressed gloss and a smooth tactile sensation. [Means for solving the problem]
[0007] The above problems are solved by the present invention as follows. Specifically, the artificial nail composition of the present invention contains component (A) a polymerizable compound, component (B) cellulose particles, and component (C) a polymerization initiator.
[0008] In one embodiment of the artificial nail composition of the present invention, it is preferable that the average particle size of the cellulose particles of component (B) is 3 to 30 μm.
[0009] In another embodiment of the artificial nail composition of the present invention, it is preferable that the content of component (B) cellulose particles is 5 to 60% by mass of the total amount of the artificial nail composition.
[0010] In other embodiments of the artificial nail composition of the present invention, it is preferable that the polymerizable compound (A) is at least one selected from the group consisting of urethane (meth)acrylate oligomers and polymerizable monomers. Furthermore, it is preferable that the urethane (meth)acrylate oligomer is at least one selected from the group consisting of urethane mono(meth)acrylate oligomers, urethane di(meth)acrylate oligomers, and urethane hexa(meth)acrylate oligomers. Furthermore, it is preferable that the polymerizable monomer is at least one selected from the group consisting of isobornyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, hydroxypropyl (meth)acrylate, triethylene glycol di(meth)acrylate, (meth)acryloylmorpholine, trimethylolpropane tri(meth)acrylate, ethoxyethylene glycol (meth)acrylate, and isoprenyl (meth)acrylate.
[0011] In another embodiment of the artificial nail composition of the present invention, it is preferable that the component (C) polymerization initiator is a photopolymerization initiator.
[0012] In other embodiments of the artificial nail composition of the present invention, it is preferable that the composition contains 39-94% by mass of component (A) polymerizable compound, 5-60% by mass of component (B) cellulose particles, and 0.1-10% by mass of component (C) polymerization initiator.
[0013] The artificial nail of the present invention is obtained from the artificial nail composition described above. In embodiments of the artificial nail of the present invention, it is preferable that the arithmetic mean roughness (Ra) of the surface is 0.2 to 1.3 μm. [Effects of the Invention]
[0014] According to the present invention, it is possible to provide an artificial nail composition for forming artificial nails that have a matte finish with suppressed gloss and a smooth texture. [Modes for carrying out the invention]
[0015] The artificial nail composition of the present invention is characterized by comprising component (A) a polymerizable compound, component (B) cellulose particles, and component (C) a polymerization initiator.
[0016] [Polymerizable compound] Component (A), a polymerizable compound, is a substance that reacts with external energy such as light or heat to form a polymer. Component (A) imparts properties such as curability, surface hardness, strength, flexibility, durability, and workability to the artificial nail composition of the present invention. Component (A) is not particularly limited as long as it is a compound having an ethylenically unsaturated group as a polymerizable functional group (e.g., polymerizable monomers, oligomers, and polymers), and known polymerizable compounds can be used. Specific examples of ethylenically unsaturated groups include, but are not limited to, (meth)acryloyl group, (meth)acryloyloxy group, (meth)acrylamide group, isoprenyl group, vinyl group, vinyl ether group, methyl vinyl ether group, allyl group, allyl ether group, and maleimide group. Among these, from the viewpoint of curability, surface hardness, strength, flexibility, and durability, it is preferable that at least one is selected from the group consisting of (meth)acryloyl group, (meth)acryloyloxy group, and isoprenyl group.
[0017] In this specification, the term (meth)acryloyl encompasses both acryloyl and methacryloyl, the term (meth)acrylate encompasses both acrylate and methacrylate, the term (meth)acryloyloxy encompasses both acryloyloxy and methacryloyloxy, and the term (meth)acrylamide encompasses both acrylamide and methacrylamide.
[0018] Specific examples of component (A) having one ethylenically unsaturated group in one molecule include methacrylic acid, acrylic acid, urethane mono(meth)acrylate, methoxyethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, ethoxyethylene glycol (meth)acrylate, ethoxypolyethylene glycol (meth)acrylate, phenoxyethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxypropyl hexaphthalic acid, stearyl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth) Examples include, but are not limited to, polymerizable monomers such as acrylate, hydroxybutyl (meth)acrylate, 3-chloro-2-hydroxypropyl (meth)acrylate, isobornyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, 2-(meth)acryloyloxyethyl dihydrogen phosphate, 2-(meth)acryloyloxyethyl phenyl hydrogen phosphate, 10-(meth)acryloyloxydecyl dihydrogen phosphate, 6-(meth)acryloyloxyhexyl dihydrogen phosphate, 2-(meth)acryloyloxyethyl 2-bromoethyl hydrogen phosphate, methylol (meth)acrylamide, dimethyl (meth)acrylamide, (meth)acryloylmorpholine, and vinyl chloride; oligomers of the polymerizable monomers; and polymers of the polymerizable monomers. The oligomer and polymer may contain one of the exemplary polymerizable monomers, or two or more. These may be used individually or in combination of two or more.
[0019] In this specification, the term "oligomer" refers to a polymer formed by the polymerization of 2 to several tens of polymerizable monomers. The term "polymer" refers to a polymer formed by the polymerization of several tens or more polymerizable monomers, excluding oligomers.
[0020] Specific examples of component (A) having two ethylenically unsaturated groups in one molecule include urethane di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 2-methyl-1,8-octanediol di(meth)acrylate, glycerin di(meth)acrylate, ethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, and polypropylene Examples include, but are not limited to, polymerizable monomers such as ethylene glycol di(meth)acrylate, ethoxylated polypropylene glycol di(meth)acrylate, ethoxylated propylene glycol di(meth)acrylate, ethoxylated bisphenol A di(meth)acrylate, propoxylated bisphenol A di(meth)acrylate, propoxylated ethoxylated bisphenol A di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, isoprenyl(meth)acrylate, and bis[2-(methacryloyloxy)ethyl] phosphate; oligomers of the polymerizable monomers; and polymers of the polymerizable monomers. The oligomers and polymers may contain one of the exemplary polymerizable monomers, or two or more. These may be used individually or in combination of two or more.
[0021] Specific examples of the component (A) having 3 or more ethylenically unsaturated groups in one molecule include polymerizable monomers such as urethane tri(meth)acrylate, urethane tetra(meth)acrylate, urethane penta(meth)acrylate, urethane hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, ethoxylated glycerin tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, propoxylated pentaerythritol tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, ethoxylated isocyanuric acid tri(meth)acrylate, tetramethylolmethane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, caprolactone-modified pentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and caprolactone-modified pentaerythritol hexa(meth)acrylate; oligomers of the aforementioned polymerizable monomers; polymers of the aforementioned polymerizable monomers, and the like, but are not limited thereto. The oligomer and the polymer may contain one kind of the polymerizable monomers exemplified above, or may contain two or more kinds thereof. These may be used alone, or in combination of two or more kinds.
[0022] The molecular weight (Mw) of the polymerizable monomer of the aforementioned component (A) is not particularly limited, but is preferably less than 1,000. The weight average molecular weight (Mw) of the oligomer of the aforementioned component (A) is not particularly limited, and is, for example, 30,000 or less, preferably 200 to 30,000, more preferably 300 to 30,000, and even more preferably 700 to 10,000. The weight average molecular weight (Mw) of the polymer of the aforementioned component (A) is not particularly limited, and is, for example, more than 30,000, preferably more than 30,000 and 100,000 or less. Within this range, properties such as curability, surface hardness, strength, flexibility, and durability can be improved. In addition, in the present specification, as the weight average molecular weight (Mw), a value measured by gel permeation chromatography (GPC) using polystyrene as a standard substance is adopted.
[0023] The aforementioned polymerizable monomer is preferably a liquid under an atmosphere of 23°C and has fluidity. Specifically, for the aforementioned polymerizable monomer, the shear rate at 23°C measured using a rheometer which is a dynamic viscoelasticity measuring apparatus is 10 s -1 The viscosity at this point is preferably 20,000 mPa·s or less, more preferably 10,000 mPa·s or less, even more preferably 5,000 mPa·s or less, and particularly preferably 1,000 mPa·s or less. The aforementioned oligomer may or may not have fluidity under an atmosphere of 23°C. Specifically, for the aforementioned oligomer, the shear rate at 23°C measured using a rheometer which is a dynamic viscoelasticity measuring apparatus is 10 s -1 The viscosity at this point is preferably 7,000 mPa·s or more, more preferably 7,000 to 3,000,000 mPa·s, even more preferably 7,000 to 2,500,000 mPa·s, and particularly preferably 7,000 to 2,200,000 mPa·s. The aforementioned polymer may or may not have fluidity under an atmosphere of 23°C.
[0024] The component (A) can also be composed of two or more types. Among the examples, it is preferable to use at least one selected from the group consisting of methacrylic acid, acrylic acid, urethane mono(meth)acrylate, urethane di(meth)acrylate, urethane tri(meth)acrylate, urethane tetra(meth)acrylate, urethane penta(meth)acrylate, urethane hexa(meth)acrylate, isobornyl(meth)acrylate, tetrahydrofurfuryl(meth)acrylate, hydroxypropyl(meth)acrylate, triethylene glycol di(meth)acrylate, (meth)acryloylmorpholine, bis[2-(methacryloyloxy)ethyl] phosphate, trimethylolpropane tri(meth)acrylate, ethoxyethylene glycol(meth)acrylate, isoprenyl(meth)acrylate, oligomers thereof, and polymers thereof. The oligomers and polymers may contain one of the polymerizable monomers of the examples above as constituent units, or they may contain two or more. Furthermore, component (A) more preferably comprises the oligomer and the polymerizable monomer, and more preferably comprises at least one urethane (meth)acrylate oligomer selected from the group consisting of urethane mono(meth)acrylate oligomer, urethane di(meth)acrylate oligomer, and urethane hexa(meth)acrylate oligomer, and at least one polymerizable monomer selected from the group consisting of isobornyl(meth)acrylate, tetrahydrofurfuryl(meth)acrylate, hydroxypropyl(meth)acrylate, triethylene glycol di(meth)acrylate, (meth)acryloylmorpholine, trimethylolpropane tri(meth)acrylate, ethoxyethylene glycol(meth)acrylate, and isoprenyl(meth)acrylate, and particularly preferably comprises urethane di(meth)acrylate oligomer and at least one polymerizable monomer selected from the group consisting of isobornyl(meth)acrylate and triethylene glycol di(meth)acrylate. By including the oligomer and the polymerizable monomer in component (A), properties such as curability, surface hardness, strength, flexibility, durability, and workability can be improved.
[0025] Although there are no particular restrictions on the content of component (A), it is preferable that the content of component (A) relative to the total amount of the composition be in the range of 39 to 94% by mass, more preferably in the range of 49 to 89% by mass, and even more preferably in the range of 49 to 79% by mass. By keeping it within this range, properties such as matte finish, tactile feel, non-adhesion, stain resistance, transparency, surface hardness, strength, flexibility, durability, and workability can be improved.
[0026] [Cellulose particles] Component (B), cellulose particles, impart a matte finish with suppressed gloss and a smooth texture to the artificial nail composition of the present invention. Furthermore, it improves adhesion and stain resistance, and provides properties such as transparency, strength, flexibility, durability, and workability.
[0027] The aforementioned component (B) is a particle mainly composed of cellulose or cellulose acetate, and can be used without any limitations as long as it does not dissolve in other components. Furthermore, there are no particular restrictions on the shape of the aforementioned component (B), and any particle shape such as spherical, needle-shaped, plate-shaped, crushed, or flaky can be used without any limitations. Among these, a spherical shape is preferred.
[0028] There are no particular restrictions on the structure of component (B), and any structure can be used, such as porous, non-porous, solid, hollow, or core-shell structures. Among these, non-porous is preferred.
[0029] Although there are no particular restrictions on the average particle size of component (B), it is preferably in the range of 3 to 30 μm, more preferably in the range of 3 to 20 μm, and even more preferably in the range of 5 to 10 μm. By keeping it within this range, it is possible to improve matte finish, tactile feel, non-adhesion, stain resistance, transparency, and durability.
[0030] In this specification, the term "average particle diameter" refers to the value of the 50% cumulative volume particle diameter obtained by measuring the particle size distribution with a laser diffraction particle size analyzer.
[0031] Although there are no particular restrictions on the content of component (B), it is preferably in the range of 5 to 60% by mass, more preferably 10 to 50% by mass, and even more preferably 20 to 35% by mass, relative to the total amount of the composition. By keeping it within this range, it is possible to improve matte finish, tactile feel, non-adhesion, stain resistance, transparency, strength, flexibility, durability, and workability.
[0032] [Polymerization initiator] Component (C), the polymerization initiator, is a compound for initiating the polymerization reaction of component (A). There are no particular restrictions on the type of component (C), and known polymerization initiators can be used. Examples of component (C) include photopolymerization initiators that initiate the polymerization reaction by irradiation with energy rays such as visible light, ultraviolet light, X-rays, and electron beams; thermal polymerization initiators that initiate the polymerization reaction by heating to a certain temperature or higher; and chemical polymerization initiators of the type that involve mixing two or more components to initiate the polymerization reaction by mixing specific substances, but photopolymerization initiators are preferred. Examples of photopolymerization initiators include radical polymerization initiators that generate radicals by irradiation with energy rays, cationic polymerization initiators that generate cations, and anionic polymerization initiators that generate anions, but radical polymerization initiators are preferred. Specific examples of radical photopolymerization initiators include, but are not limited to, benzoin ethers, benzyl ketals, α-dialkoxyacetophenones, α-hydroxyalkylphenones, α-aminoalkylphenones, acylphosphine oxides, benzophenones, thioxanthones, and titanocenes. Furthermore, it is possible to select two or more of these polymerization initiators to construct an artificial nail composition. In particular, it is preferable to use at least one selected from the group consisting of α-hydroxyalkylphenones and acylphosphine oxides.
[0033] Specific examples of α-hydroxyalkylphenones include 1-hydroxycyclohexylphenyl ketone, 2-hydroxy-2-methyl-1-phenylpropan-1-one, and α-aminoalkylphenone. Specific examples of acylphosphine oxides include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylphenylethoxyphosphine oxide, and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide. Among these, it is preferable to use at least one selected from 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylphenylethoxyphosphine oxide, and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.
[0034] Although there are no particular restrictions on the content of component (C), it is preferably in the range of 0.1 to 10% by mass, more preferably in the range of 0.1 to 6% by mass, and even more preferably in the range of 0.5 to 6% by mass, relative to the total amount of the composition. By keeping it within these ranges, properties such as curability, surface hardness, strength, flexibility, and durability can be improved.
[0035] [Other ingredients] The artificial nail composition of the present invention may contain components other than those described above (A) to (C), as long as they do not impair the effects of the present invention. Other components include auxiliaries, additives, colorants, leveling agents, plasticizers, antioxidants, polymerization accelerators, polymerization inhibitors, flocculants, preservatives, waxes, thickeners, fragrances, UV shielding agents, diffusing agents, defoaming agents, dispersants, fillers, surfactants, pigments, dyes, excipients, ion release agents, antibacterial agents, chain transfer agents, and silane coupling agents, which are widely used in artificial nail compositions. These may be used individually or in combination of two or more types.
[0036] As polymerization accelerators, polyfunctional thiol compounds having two or more thiol groups in one molecule can be used. By using polyfunctional thiol compounds, the curing reaction proceeds without being inhibited by oxygen. Specific examples of polyfunctional thiol compounds include 1,2-ethanedithiol, 1,2-propanedithiol, 1,3-propanedithiol, 1,3-butanedithiol, 2,3-butanedithiol, 1,5-pentanedithiol, 1,6-hexanedithiol, 1,8-octanedithiol, 1,9-nonanedithiol, 1,10-decanedithiol, 1,2-benzenedithiol, 1,3-benzenedithiol, 1,4-benzenedithiol, and 3,6-dichloro-1,2-benzenedithiol. All, Toluene-3,4-dithiol, 1,5-naphthalenedithiol, ethylene glycol bis(thioglycolate), ethylene glycol bis(3-mercaptopropionate), 1,4-butanediol bisthioglycolate, tetraethylene glycol bis(3-mercaptopropionate), trimethylolpropane tris(thioglycolate), trimethylolpropane tris(3-mercaptopropionate), trimethylolpropane tris(3-mercaptobutyrate), tris [(3-mercaptopropionyloxy)-ethyl]isocyanurate, pentaerythritol tetrakis(thioglycolate), pentaerythritol tetrakis(3-mercaptopropionate), dipentaerythritol hexakis(3-mercaptopropionate), 1,4-bis(3-mercaptobutyryloxy)butane, pentaerythritol tetrakis(3-mercaptobutyrate), 1,3,5-tris(3-mercaptobutyloxyethyl)-1,3,5-triazine-2,4,6 (1H,3H,5H)-Trion, Dimercaptodiethyl sulfide, 1,8-Dimercapto-3,6-Dithiaoctane, 1,2-Bis[(2-Mercaptoethyl)thio]-3-Mercaptopropane, Tetrakis(7-Mercapto-2,5-Dithiaheptyl)methane, Trithiocyanuric acid, 1,2-Benzenedimethane, Thiol, 4,4'-Thiobisbenzenethiol, 2-Di-n-Butylamino-4,6-Dimercapto-s-Triadin, 2,5-Dimercapto-1,3,4-Thiadianazole, 1,8-Dimercapto-3,6-Dioxaoctane, 1,5-Dimercapto-3-Tiapentane, Tris(2-Hydroxyethyl)Isocyanurate Trimercaptopropionate, 1,4-Dimethylmercaptobenzene, 2,4,6-Trimercapto-s-Triazine, 2-(N,N-Dibutylamino)-4,6-Dimercapto-s-Triazine, Bis(4-(2-Mercaptopropoxy)phenyl)methane, 1,1-Bis(4-(2-Mercaptopropoxy)phenyl)ethane, 2,2-Bis(4-(2-Mercaptopropoxy)phenyl)propane, 2,2-Bis(4-(2-Mercaptopropoxy)phenyl)butane, 1,1-Bis(4-(2-Mercaptopropoxy)phenyl)isobutane, 2,2-Bis(4-(2-Mercaptopropoxy) Examples include tris(4-(2-mercaptopropoxy)-5-methylphenyl)propane, 2,2-bis(4-(2-mercaptopropoxy)-5-methylphenyl)propane, bis(2-(2-mercaptopropoxy)-5-methylphenyl)methane, 2,2-bis(4-(2-mercaptopropoxy)-3-t-butylphenyl)propane, tris(4-(2-mercaptopropoxy)phenyl)methane, 1,1,1-tris(4-(2-mercaptopropoxy)phenyl)ethane, bis(4-(2-mercaptobutoxy)phenyl)methane, 2,2-bis(4-(2-mercaptobutoxy)phenyl)propane, tris(4-(2-mercaptobutoxy)phenyl)methane, 1,3,5-triazine-2,4,6-trithiol, and alkyl vinyl ether adducts thereof. However, the list is not limited to these. These polymerization accelerators may be used individually or in combination of two or more types.
[0037] In addition to polyfunctional thiol compounds, tertiary amines can also be used as polymerization accelerators. Specific examples of tertiary amines include N,N-dimethylaniline, N,N-diethylaniline, N,N-di-n-butylaniline, N,N-dibenzylaniline, N,N-dimethyl-p-toluidine, N,N-dimethyl-m-toluidine, N,N-diethyl-p-toluidine, p-bromo-N,N-dimethylaniline, m-chloro-N,N-dimethylaniline, p-dimethylaminobenzaldehyde, p-dimethylaminoacetophenone, p-dimethylaminobenzoic acid, p-dimethylaminobenzoic acid ethyl ester, p-dimethylaminobenzoic acid amino ester, N,N-dimethylanthranic acid methyl ester, and N,N-dihydrox Examples include cyethylaniline, N,N-dihydroxyethyl-p-toluidine, p-dimethylaminophenyl alcohol, p-dimethylaminostyrene, N,N-dimethyl-3,5-xylidine, 4-dimethylaminopyridine, N,N-dimethyl-α-naphthylamine, N,N-dimethyl-β-naphthylamine, tributylamine, tripropylamine, triethylamine, N-methyldiethanolamine, N-ethyldiethanolamine, N,N-dimethylhexylamine, N,N-dimethyldodecylamine, N,N-dimethylstearylamine, N,N-dimethylaminoethyl methacrylate, N,N-diethylaminoethyl methacrylate, and 2,2'-(n-butylimino)diethanol. However, the list is not limited to these. These polymerization accelerators may be used individually or in combination of two or more types.
[0038] The artificial nail composition of the present invention can be applied to, but is not limited to, natural nails, nails with a coating formed by the artificial nail composition, artificial resin tips, resin films, and resin sheets. Furthermore, while there are methods of application, such as brushes, sponges, sprays, inkjet printers, air knives, and rollers, the invention is not limited to these.
[0039] While there are no particular limitations on the viscosity of the artificial nail composition of the present invention, it is preferable that it be fluid in a 23°C atmosphere from the viewpoint of operability. Specifically, the viscosity of the artificial nail composition of the present invention is measured using a rheometer, which is a dynamic viscoelasticity measuring device, at 23°C and a shear rate of 10s. -1 The viscosity is preferably 50,000 mPa·s or less, more preferably 10,000 mPa·s or less, and even more preferably 5,000 mPa·s or less. On the other hand, the lower limit of viscosity is not particularly limited, but it is preferably 1 mPa·s or more, more preferably 10 mPa·s or more, even more preferably 100 mPa·s or more, particularly preferably 1,000 mPa·s or more, and most preferably 1,500 mPa·s or more. The viscosity of the artificial nail composition of the present invention can be adjusted by appropriately adjusting the types and contents of the above components (A) to (C).
[0040] While there are no particular restrictions on the surface roughness of the artificial nail (cured body) obtained from the artificial nail composition of the present invention, from the viewpoint of matte finish, tactile feel, poor adhesion, and stain resistance, the arithmetic mean roughness (Ra) of the surface is preferably in the range of 0.2 to 1.3 μm, more preferably 0.4 to 1.0 μm, and even more preferably 0.5 to 0.8 μm. In this specification, the arithmetic mean roughness (Ra) of the surface of the artificial nail (cured body) is calculated by the following method. The artificial nail composition is applied to a glass plate using a spacer, cured by irradiating with light for 20 seconds using a gel nail light (manufactured by Nail Lab Co., Ltd., product name: PRESTO LED light), and then the unpolymerized surface layer of the artificial nail composition is removed using tissue paper soaked in ethanol to create a thin film with a thickness of 0.2 mm, a long side of 50.0 mm, and a short side of 15.0 mm. For no-wipe type artificial nail compositions that do not require removal of the unpolymerized surface layer, the wiping step is omitted. Next, in accordance with "4.2.1" of JIS B0601:2013 (Geometric product specifications (GPS) - Surface texture: contour curve method - Terms, definitions and surface texture parameters), surface roughness measurements were performed at three arbitrary locations on the fabricated thin film using a stylus-type surface roughness measuring instrument (Tokyo Seimitsu Co., Ltd., model: Surfcom 1500SD), and the average value was adopted as the arithmetic mean roughness (Ra).
[0041] There are no particular limitations on the type of artificial nail composition of the present invention, and examples include nail polish, gel nails, and acrylic nails. Nail polish is a paint for nails, also known as nail lacquer, nail enamel, or manicure, and is a composition that creates a coating film with excellent aesthetic appearance by drying the solvent it contains. Gel nails are materials containing resin components that harden with ultraviolet or visible light, and are compositions that create a coating film with excellent aesthetic appearance by being applied to natural or artificial nails and then cured by irradiation with ultraviolet or visible light. Acrylic nails are powder-liquid materials containing polymer beads and polymerizable monomers, and are compositions that harden after mixing the powder and liquid, as polymerization of the polymerizable monomers is initiated by the peroxide contained in the polymer beads. Acrylic nails are characterized by the fact that they can be built up and shaped not only by application, and are often used mainly for nail growth. Among these, the artificial nail composition of the present invention is preferably gel nail. By using gel nail for the artificial nail composition of the present invention, it is possible to form artificial nails with a matte finish that suppresses gloss and a smooth texture.
[0042] The gel nails described above are generally constructed by laminating a base layer, a color layer, and a top coat layer in that order onto natural nails or a substrate to form a coating film. There are no particular restrictions on how the artificial nail composition of the present invention is applied, and it can be used as any of the base layer, color layer, or top coat layer. From the viewpoint of being able to most prominently express the characteristics of the artificial nail composition of the present invention, namely its matte finish with suppressed gloss and smooth texture, it is preferable to use the artificial nail composition of the present invention as a top coat layer. Furthermore, from the viewpoint of being able to provide a matte finish with suppressed gloss, a smooth texture, poor adhesion that makes it difficult for mirror powder to adhere, and transparency, it is also preferable to use the artificial nail composition of the present invention as a base layer when applying nail art.
[0043] The aforementioned gel nails include those for use on fingernails, toenails, and animals. There are no particular restrictions on the use of the artificial nail composition of the present invention, and it can be used for any of the following: for hands, feet, or animals. [Examples]
[0044] Examples and comparative examples of the present invention will be described below in detail, but the present invention is not limited to these examples.
[0045] [Ingredients used in the preparation of the artificial nail composition] The components used in the preparation of the artificial nail compositions for the examples and comparative examples are shown below. The weight-average molecular weight (Mw) was measured using gel permeation chromatography (GPC) with a GPC analyzer (Shimadzu Corporation, product name: Nexera GPC system), a column (Waters, product name: Styragel HR), tetrahydrofuran as the eluent, and polystyrene as the standard substance. The average particle size was determined by measuring the particle size distribution with a laser diffraction particle size analyzer, and the value of the 50% cumulative volume particle size was adopted.
[0046] The abbreviations shown in Tables 1 to 5 are as follows: A1: Urethane diacrylate oligomer (weight-average molecular weight: 6000) A2: Urethane diacrylate oligomer (weight-average molecular weight: 8400) A3: Urethane diacrylate oligomer (weight-average molecular weight: 1000) A4: Triethylene glycol dimethacrylate A5: Isobornyl methacrylate A6: Acryloylmorpholin A7: Tetrahydrofurfuryl methacrylate A8: Trimethylolpropane triacrylate B1: Cellulose particles (Viscopal D-3, average particle size: 3 μm, manufactured by Rengo Co., Ltd.) B2: Cellulose particles (CELLULOBEADS D-5, average particle size: 5 μm, manufactured by Daito Chemical Industries, Ltd.) B3: Cellulose acetate particles (BELLOCEA S7, average particle size: 7 μm, manufactured by Daicel Corporation) B4: Cellulose particles (CELLULOBEADS D-10, average particle size: 10 μm, manufactured by Daito Chemical Industries, Ltd.) B5: Cellulose particles (CELLULOBEADS D-30, average particle size: 30 μm, manufactured by Daito Chemical Industries, Ltd.) B'1: Acrylic polymer particles (Gantzpearl GMX-0810, average particle size: 8μm, manufactured by Aica Kogyo Co., Ltd.) C1: 2,4,6-Trimethylbenzoyldiphenylphosphine oxide C2: 2,4,6-Trimethylbenzoylphenylethoxyphosphine oxide C3: Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide R-SH: Pentaerythritol tetrakis(3-mercaptopropionate)
[0047] [Preparation of artificial nail composition] According to the respective mixing ratios listed in Tables 1 to 5, each component was calculated, and the artificial nail compositions of the examples and comparative examples were prepared by mixing them under atmospheric pressure using a rotation-orbit mixer (Sinky Co., Ltd., product name: ARV-310P) until a uniform liquid was obtained.
[0048] The evaluation methods for the artificial nail compositions of the examples and comparative examples are as follows. All evaluations were performed at room temperature (23±2°C), humidity (50±10%), and under indoor LED lighting.
[0049] [Test Example 1: Evaluation of Matte Finish] The artificial nail compositions of the examples and comparative examples were applied to a glass plate using a spacer and cured by irradiating with a gel nail light (manufactured by Nail Lab Co., Ltd., product name: PRESTO LED light) for 20 seconds. Then, the unpolymerized surface layer of the artificial nail composition was removed using tissue paper soaked in ethanol to prepare a thin film with a thickness of 0.2 mm, a long side of 50.0 mm, and a short side of 15.0 mm. For Example 18, a no-wipe type that does not require removal of the unpolymerized surface layer, the wiping step was omitted. Next, the 60° gloss was measured using a gloss meter (manufactured by Horiba, Ltd., model: HORIBA Gloss Checker IG-331). In addition, three thin films were prepared for each artificial nail composition and the matte finish was evaluated. The matte finish evaluation value is the average value of the gloss of the three thin films, and a value of 30.0 or less is considered to have a matte finish, 10.0 or less is preferable, and 5.0 or less is even more preferable.
[0050] [Test Example 2: Transparency Evaluation] The artificial nail compositions of the examples and comparative examples were applied to a glass plate using a spacer, cured by irradiating with a gel nail light (Nail Lab Co., Ltd., product name: PRESTO LED light) for 20 seconds, and then the unpolymerized surface layer of the artificial nail composition was removed using tissue paper soaked in ethanol to create a thin film with a thickness of 0.2 mm, a long side of 50.0 mm, and a short side of 15.0 mm. For Example 18, a no-wipe type that did not require removal of the unpolymerized surface layer, the wiping step was omitted. Next, 10 nail technicians certified by the Japan Nailist Association visually evaluated the transparency of the thin film, and the evaluation results were brought together according to the following criteria for an overall evaluation. If the overall evaluation is A or B, the transparency can be said to be good. <Evaluation Criteria> A: The cloudiness is not a problem. B: Slightly cloudy C: It is cloudy and opaque. D: Not eligible for evaluation because it does not have a matte finish.
[0051] [Test Example 3: Tactile Test] The artificial nail compositions of the examples and comparative examples were applied to a glass plate using a spacer, cured by irradiating with a gel nail light (Nail Lab Co., Ltd., product name: PRESTO LED light) for 20 seconds, and then the unpolymerized surface layer of the artificial nail composition was removed using tissue paper soaked in ethanol to create a thin film with a thickness of 0.2 mm, a long side of 50.0 mm, and a short side of 15.0 mm. For Example 18, a no-wipe type that did not require removal of the unpolymerized surface layer, the wiping step was omitted. Next, 10 nail technicians certified by the Japan Nailist Association touched the light-irradiated surface of the thin film with fingertips cleaned with ethanol and performed a sensory evaluation of the tactile feel of the thin film. The evaluation results were then compiled according to the following criteria and an overall evaluation was performed. An overall evaluation of A or B indicates that the tactile feel is good. <Evaluation Criteria> A: It has an extremely smooth and silky texture. B: Has a smooth, silky texture. C: Has a rough, unsmooth texture. D: Has a rough, powdery texture. E: Not eligible for evaluation because it does not have a matte finish.
[0052] [Test Example 4: Surface Roughness Measurement] The artificial nail compositions of the examples and comparative examples were applied to a glass plate using a spacer, cured by irradiating with a gel nail light (manufactured by Nail Lab Co., Ltd., product name: PRESTO LED light) for 20 seconds, and then the unpolymerized surface layer of the artificial nail composition was removed using tissue paper soaked in ethanol to prepare a thin film with a thickness of 0.2 mm, a long side of 50.0 mm, and a short side of 15.0 mm. For Example 18, a no-wipe type that does not require removal of the unpolymerized surface layer, the wiping step was omitted. Next, in accordance with "4.2.1" of JIS B0601:2013 (Geometric product specifications (GPS) - Surface properties: contour curve method - terms, definitions and surface property parameters), surface roughness measurements were performed at three arbitrary locations on the prepared thin films using a stylus-type surface roughness measuring instrument (manufactured by Tokyo Seimitsu Co., Ltd., model: Surfcom 1500SD), and the average value was adopted as the arithmetic mean roughness (Ra).
[0053] [Test Example 5: Poor adhesion of mirror powder] The artificial nail compositions of the examples and comparative examples were applied to a glass plate using a spacer, cured by irradiating with a gel nail light (Nail Lab Co., Ltd., product name: PRESTO LED light) for 20 seconds, and then the unpolymerized surface layer of the artificial nail composition was removed using tissue paper soaked in ethanol to create a thin film with a thickness of 0.2 mm and dimensions of 15.0 mm on both sides. For Example 18, a no-wipe type where removal of the unpolymerized surface layer is unnecessary, the wiping step was omitted. Next, 10 nail technicians certified by the Japan Nailist Association sprinkled 5 mg of commercially available mirror powder (ageha mirror powder gold M-2) evenly onto the light-irradiated surface of the thin film, removed it using a commercially available nail duster brush (PriAnfa dust brush), and visually evaluated the adhesion of the mirror powder. The evaluation results were then compiled according to the following criteria and an overall evaluation was performed. From the viewpoint of using the artificial nail composition as a base layer for art, an overall evaluation of A or B is preferable, and A is more preferable. <Evaluation Criteria> A: I was able to remove the mirror powder within 10 brush strokes. B: The mirror powder was removed between 11 and 30 brushing sessions. C: Mirror powder remained even after brushing more than 30 times.
[0054] [Test Example 6: Viscosity Measurement] Viscosity measurements were performed on the artificial nail compositions of the examples and comparative examples using a rheometer (Anton Paar, model: Physica MCR 301), a dynamic viscoelasticity measuring device, under the following measurement conditions, with a shear rate of 10 s. -1 The measured values were defined as viscosity values. (Measurement conditions) Measurement jig: Parallel plate PP20 Shear rate: 0.1~100s -1 Measurement temperature: 23℃
[0055] (Evaluation results of the examples and comparative examples) Tables 1 to 5 show the measurement and evaluation results for matte finish, transparency, tactile feel, arithmetic mean roughness, poor adhesion of mirror powder, and viscosity for each example and comparative example.
[0056] [Table 1]
[0057] [Table 2]
[0058] [Table 3]
[0059] [Table 4]
[0060] [Table 5]
[0061] As is clear from Tables 1 to 5, each artificial nail composition in the examples had a matte finish and a smooth texture, as well as good transparency, poor adhesion of mirror powder, and good handling properties. On the other hand, each artificial nail composition in the comparative examples could not achieve both a matte finish and a smooth texture. [Industrial applicability]
[0062] According to the present invention, it is possible to provide an artificial nail composition having a matte finish with suppressed gloss and a smooth texture.
Claims
1. Component (A): Polymerizable compound Ingredient (B): Cellulose particles Ingredient (C): Polymerization initiator An artificial nail composition containing the following:
2. The artificial nail composition according to claim 1, wherein the average particle size of the cellulose particles of component (B) is 3 to 30 μm.
3. The artificial nail composition according to claim 1, wherein the content of component (B) cellulose particles is 5 to 60% by mass with respect to the total amount of the artificial nail composition.
4. The artificial nail composition according to claim 1, wherein the polymerizable compound (A) is at least one selected from the group consisting of urethane (meth)acrylate oligomers and polymerizable monomers.
5. The artificial nail composition according to claim 4, wherein the urethane (meth)acrylate oligomer is at least one selected from the group consisting of urethane mono (meth)acrylate oligomer, urethane di (meth)acrylate oligomer, and urethane hexa (meth)acrylate oligomer.
6. The artificial nail composition according to claim 4, wherein the polymerizable monomer is at least one selected from the group consisting of isobornyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, hydroxypropyl (meth)acrylate, triethylene glycol di(meth)acrylate, (meth)acryloylmorpholine, trimethylolpropane tri(meth)acrylate, ethoxyethylene glycol (meth)acrylate, and isoprenyl (meth)acrylate.
7. The artificial nail composition according to claim 1, wherein the component (C) polymerization initiator is a photopolymerization initiator.
8. Component (A): Polymerizable compound 39-94% by mass Ingredient (B): Cellulose particles 5-60% by mass Component (C): Polymerization initiator 0.1-10% by mass The artificial nail composition according to claim 1, comprising:
9. An artificial nail obtained from the artificial nail composition according to any one of claims 1 to 8.
10. The artificial nail according to claim 9, wherein the artificial nail has an arithmetic mean roughness (Ra) of 0.2 to 1.3 μm.
Citation Information
Patent Citations
Claws are light-cured resin compositions used for artificial claws.
JP7014970B2